2020
DOI: 10.1071/fp19025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N supply on the carbon economy of barley when accounting for plant size

Abstract: Nitrogen availability and ontogeny both affect the relative growth rate (RGR) of plants. In this study of barley (Hordeum vulgare L.) we determined which growth parameters are affected by nitrate (N) availability, and whether these were confounded by differences in plant size, reflecting differences in growth. Plants were hydroponically grown on six different nitrate (N) concentrations for 28 days, and nine harvests were performed to assess the effect of N on growth parameters. Most growth parameters showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…The nutritional growth of plants is influenced by many intrinsic and extrinsic factors, and productivity can be effectively increased by changing some of them [35,36]. Numerous studies have demonstrated that exogenous N addition is one of the most effective ways to increase productivity [37,38], and the results of this work were consistent with the fact that N addition to the nutrient solution increased the growth of pecan to varying degrees compared to the N deficiency treatment (Figure 1B,D).…”
Section: Comprehensive Evaluation Of Photosynthesis and Growth Of Pecansupporting
confidence: 84%
“…The nutritional growth of plants is influenced by many intrinsic and extrinsic factors, and productivity can be effectively increased by changing some of them [35,36]. Numerous studies have demonstrated that exogenous N addition is one of the most effective ways to increase productivity [37,38], and the results of this work were consistent with the fact that N addition to the nutrient solution increased the growth of pecan to varying degrees compared to the N deficiency treatment (Figure 1B,D).…”
Section: Comprehensive Evaluation Of Photosynthesis and Growth Of Pecansupporting
confidence: 84%
“…The application of N fertilizer is an important way to improve the productivity of cash crops ( Negrini et al., 2020 ). However, the effect of different forms of N fertilizer on plant growth is different ( Nicodemus et al., 2008 ; Lang et al., 2018 ; Qin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore empirical evidence conflicts on whether root:shoot ratios should increase or decrease from changes in CO 2 and soil nitrogen availability. An emergent property of the model is the decline in root:shoot ratio with age and is seen commonly in plants (Poorter et al, 1988;Negrini et al, 2020). Another emergent property of the model is that low N availability produces small plants with reasonable intermediate concentrations of carbon and nitrogen (Wu et al, 2007) rather than the alternative of producing larger plants with a diluted nitrogen content and consequences of functioning (Vos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%